Cultivation potential of Vanilla crop wild relatives in two contrasting land use systems - Watteyn, Charlotte (2023)
Vanilla is an important cash crop for many smallholder farmers around the tropics, and a highly appreciated spice used in a wide range of products. The crop species Vanilla planifolia is, however, facing a number of threats that are jeopardizing a stable vanilla supply. The neotropical realm holds at least 37 fragrant Vanilla species besides V. planifolia. These so-called Vanilla crop wild relatives (CWRs) possibly possess interesting traits for crop improvement and market diversification, but received meager attention so far. The aim of our study was therefore to provide insights into the cultivation potential of four Vanilla CWRs (Vanilla hartii, V. odorata, V. pompona and V. trigonocarpa) naturally growing within our study region in southern Costa Rica, by comparing their plant performance and aromatic profiles with V. planifolia and a commercially used hybrid, and this in two types of land use systems where vanilla could possibly be introduced. As such, we established six field sites in secondary forests (SF), adding economic value to these often undervalued ecosystems, and six in existing cacao plantations (CP), diversifying monocrop agrosystems. First, we measured plant survival, vitality and growth over a period of two years, and compared these plant performance traits among Vanilla species and land use systems using (generalized) additive mixed models. The models also enabled us to observe possible effects of additionally measured, site-specific environmental variables on vanilla plant performance. Second, we evaluated the aromatic potential of Vanilla CWR pods using high-performance liquid chromatography. We found that the hybrid had the highest overall plant vitality and growth, and this in both CPs and SFs, while V. planifolia was characterized by a rather low vitality, but high growth rates, and clearly performed inferior in SFs. The CWRs had a good overall vitality, and this in the two land use systems, but were characterized by lower growth rates compared to the hybrid and V. planifolia. The aromatic profiles of the Vanilla CWR pods indicated potential for market diversification, with V. odorata highly resembling the profile of the commercially used species. The other CWRs had varied profiles, with especially V. hartii containing high anisyl contents interesting for niche markets. Based on our assessment of Vanilla CWR plant performance and aromatic profiles, we see potential for their integration within the two studied land use systems. Corresponding planting designs should, however, take into account species-specific light intensity preferences, monitor chemical properties and the presence of growth-promoting and disease-suppressive soil microbiota, and incorporate vanilla tutor and shade trees with optimal functional traits. We developed a possible vanilla cultivation design that could be implemented for further evaluation in terms of production feasibility.